Haplotypes of susceptibility to chronic periodontitis do not influence MMP-8 levels or the outcome of non-surgical periodontal therapy - Anovazzi, Giovana [UNESP]; Medeiros, Marcell C. de [UNESP]; Ferrisse, Túlio Morandin [UNESP]; Corbi, Sâmia C. T. [UNESP]; Finoti, Lívia S. [UNESP]; Tanaka, Marcia Hiromi [UNESP]; Marcaccini, Andrea M.; Orrico, Silvana R. P. [UNESP]; Cirelli, Joni A.; Gerlach, R. F.; Caminaga, Raquel Mantuaneli Scarel [UNESP] (My University, 2014)
Introduction: Chronic periodontitis (CP) is a multifactorial condition, presenting immunoinflammatory reaction, in which a myriad of molecules including cytokines and matrix metalloproteinases (MMPs) interplays, making the system extremely intricate. There is scarce information regarding interconnections of biological influence among IL-4, IL-8 and MMP-8, mainly considering genetic polymorphisms, and also, whether this can influence the outcome of periodontal therapy. Previously, we reported that variants in the interleukin 4 (IL4) and interleukin 8 (IL8) genes were associated with CP in Brazilians. The aim of this study was to investigate, in individuals with different genetic backgrounds with regard to the IL4 or IL8 haplotypes, differences in the immunological levels of MMP-8 in gingival crevicular fluid (GCF) before and after non-surgical periodontal treatment. A total of 141 patients participated of this study, classified as susceptible or not to CP, according to the presence of haplotypes formed by polymorphysms in the IL4 or IL8 genes. All individuals received non-surgical periodontal therapy and follow–up continued for 45 days. The GCF samples were collected at baseline and on the 45th day. The MMP-8 levels were determined by ELISA. Results: No association was found between genetic backgrounds and MMP-8 levels in GCF or the outcome of non-surgical periodontal therapy. Conclusions: In this longitudinal clinical study, the presence of IL4 or IL8 haplotypes previously associated with CP did not influence the outcome of non-surgical periodontal therapy and the MMP-8 levels in the GCF. Additional studies are necessary to determine the mechanisms by which the IL4 or IL8 haplotypes affect individual susceptibility to CP.
Keywords: MMP-8; Chronic periodontitis; Disease Susceptibility; Gingival Crevicular Fluid